PENGARUH BRAND IMAGE DAN BRAND EXPERIENCE TERHADAP BEHAVORIAL INTENTION MELALUI CUSTUMER EXPERIENCE SEBAGAI MODERASI (Studi Kasus Destinasi Wisata Seribu Rumah Gadang di Muara Labuh Kecamatan Sungai Pagu Kabupaten Solok Selatan Propinsi Sumatera Barat) - Vera Septaria; Rusma Rizal (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2022)
This study aims to determine the effect of Brand Image and Brand Experience on Behavioral Intention through Customer Experience as moderation at the Thousand Houses Gadang Tourist Destination in Muara Labuh Regency, West Sumatra Province. This look at makes use of a quantitative technique with the purpose of explaining the location of the variables studied and the connection between one variable and any other. This observe is intended to test the hypotheses that have been formulated previously. The effects of this look at will provide an explanation for the causal courting between the variables through hypothesis testing. in this look at, the analytical method used is direction analysis with path evaluation using the SmartPLS application. The outcomes of this look at observed that brand experience had a full-size impact on behavioral purpose, logo picture had no huge impact on behavioral purpose. circuitously, patron experience as a mediation has no big effect on logo image on behavioral aim, consumer experience as a mediation does not substantially affect brand experience on behavioral goal, purchaser enjoy as a mediation has a vast impact on behavioral purpose